Handroanthus grandiflorus (Bignoniaceae), a new species from the semiarid region of Brazil - Santo, Fabio Da Silva Do Espírito; Da Silva-Castro, Milene Maria; Rapini, Alessandro (Phytotaxa, 2012)
Handroanthis grandiflorus, a new species of Bignoniaceae from the Caatinga biome, is described and illustrated. The species is Critically Endangered, and can be distinguished from its congeners by having a corolla with larger lobes, reaching to 6.1 × 4.3 cm. The diagnostic characters of the new species are discussed.